APPRAISAL IN THE 2013 INAUGURAL ADDRESS OF PRESIDENT BARACK OBAMA - HARISTYANTI, INDRIA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Systemic Functional Linguistics, Appraisal, Attitude, Modality, President Barack Obama, Inaugural Address. Systemic Functional Linguistics (SFL) views language as a meaning-making. Appraisal as a framework under SFL focuses on the ways the speakers construct particular identities and how they position themselves in front of people whom they are addressing. By analyzing the language that is used by the speakers, it can provide the sight of the speakers’ objectives and belief, as well as to understand their position in relation to the others. In this study, the researcher is interested to analyze the Appraisal on 2013 inaugural address delivered by President Barack Obama. There are two problems of the study that are proposed by the researcher: (1) what are the types of Affect, Judgement, and Appreciation elements used by President Barack Obama in his 2013 inaugural address?; (2) how does the attitudinal positioning function to convey the perspective of President Barack Obama?. The researcher applies a theory from Martin and White (2005) and limits the data by selecting the utterances that contain adjectives, verbs of emotion (mental process), adverbs, and modalitiesThe researcher conducted her study using qualitative approach. In collecting the data, the researcher firstly searched for the transcript of President Barack Obama’s 2013 inaugural address from the Internet. Then, she read the transcript and selected the utterances that contain Attitude elements.The study shows that President Barack Obama used all of the types of Attitude elements in his 2013 inaugural address, which are, Affect, Judgement, and Appreciation. The most dominant type of Attitude is Judgement, the second isAppreciation, and the least is Affect. Judgement of positive capacity is the expression that is often found in Obama’s inaugural address. In Appreciation, Obama mostly used positive reaction in his speech. In Affect, Obama only used the expression that are related to dis/inclination and in/security. In relation to Judgement, the type of modality that is mostly used by Obama is intrinsic modality. By using Appraisal theory to analyze the utterances in 2013 inaugural address of President Barack Obama, the researcher found that the attitudinal positioning of Obama as the speaker function to give positive perspective towards his own feelings, the behavior of American people, as well as the phenomena that occurs in United States of America.Finally, the researcher suggests the future researchers to conduct the Appraisal analysis in the other speech from English speakers. Future research also can be done by taking all of three aspects of Appraisal or only focusing on Engagement or Graduation.